Rheological Experimentation to Investigate History Dependent Viscoelastic Properties of ex-vivo Ovine Brain Tissue. Issue 2 (2020) - Lilley, Rebecca; Reynaud, Antoine; Docherty, Paul D.; Smith, Nicole; Kabaliuk, Natalia
Abstract: Much controversy exists around the issue of repetitive Traumatic Brain Injuries (TBIs) and long-term brain health. Little is known about the mechanical response of brain tissue to traumatic impacts and head accelerations. While history dependent characteristics of other biological tissues have been investigated experimentally, no methodology currently exists for investigating the mechanical response of brain tissue to cyclic loading and its fatigue properties. This investigation presents sample preparation, conditioning and rheological methodology for undertaking repetitive loading of ex-vivo ovine brain tissue. Rheological amplitude sweep tests undertaken at 3 Hz on ø10 mm by 5 mm ovine brain tissue samples, employing a periodic moisturisation and a normal force of 50 mN, yielded results agreeing with those reported in literature for low number of cycle loading and showed signs of history dependence at higher number of cycles. Understanding brain tissue response to repeated loading, fatigue properties and associated trauma mechanisms can be advances by undertaking high cycle rheological testing with the methodology presented in this article.